Identification of novel genes involved in the biofilm formation process of Avian Pathogenic Escherichia coli (APEC) - Meaghan M. Young; Aline L. de Oliveira; Lisa K. Nolan; Nicolle L. Barbieri; Catherine M. Logue (PLoS ONE, 2022)
Avian pathogenic Escherichia coli (APEC) is the etiological agent of avian colibacillosis, a leading cause of economic loss to the poultry industry worldwide. APEC causes disease using a diverse repertoire of virulence factors and has the ability to form biofilms, which contributes to the survival and persistence of APEC in harsh environments. The objective of this study was to identify genes most widespread and important in APEC that contribute to APEC biofilm formation. Using the characterized APEC O18 as the template strain, a total of 15,660 mutants were randomly generated using signature tagged mutagenesis and evaluated for decreased biofilm formation ability using the crystal violet assay. Biofilm deficient mutants were sequenced, and a total of 547 putative biofilm formation genes were identified. Thirty of these genes were analyzed by PCR for prevalence among 109 APEC isolates and 104 avian fecal E. coli (AFEC) isolates, resulting in nine genes with significantly greater prevalence in APEC than AFEC. The expression of these genes was evaluated in the wild-type APEC O18 strain using quantitative real-time PCR (qPCR) in both the exponential growth phase and the mature biofilm phase. To investigate the role of these genes in biofilm formation, isogenic mutants were constructed and evaluated for their biofilm production and planktonic growth abilities. Four of the mutants (rfaY, rfaI, and two uncharacterized genes) displayed significantly decreased biofilm formation, and of those four, one (rfaI) displayed significantly decreased growth compared to the wild type. Overall, this study identified novel genes that may be important in APEC and its biofilm formation. The data generated from this study will benefit further investigation into the mechanisms of APEC biofilm formation.